(untitled) - Lazarus, Barbara B. (New York, 2001)
Survive and thrive in graduate school. Designed to unravel some of the mystery around graduate school programs in science and engineering, this one-stop resource reinforces strategies for succeeding. Qualitative interviews offer first-hand stories and tips from women who have found success in academia, industry, and the public sector. Each chapter covers a different aspect of graduate school, from identifying funding sources, to writing the dissertation, to looking for a job. THE WOMAN'S GUIDE TO NAVIGATING THE PH.D. IN ENGINEERING & SCIENCE also focuses on the emotional and social difficulties women may experience, and offers practical suggestions and advice for surviving and thriving in graduate school.
Keywords: Women engineers,Women scientists,Engineering,Science,Nữ kỹ sư,Nhà khoa học nữ,Kỹ thuật,Khoa học; Study and teaching (Higher),Study and teaching (Higher),Học và dạy (cấp cao hơn),Học và dạy (cấp cao hơn)